Нystological changes of healing of an transversoanastomosis made by interrupted single row seromusculosubmucosal sutures - A. Shott; M. K. Nedzvedz (Military Medicine, 2026)
The aim of the study was to determine hystologicchanges of healing of antransversoanastomosis made by interrupted single row seromusculosubmucosal sutures in 30 days after a surgery in the experiment. M aterial and methods. D uring experimental surgery on 6 dogs colonicend-to-end transversoanastomoses were performed with handle interrupted mattress seromusculosubmucosal sutures using vicryl 000 with atraumatic needles. In terms of 2, 6 and 30 days after the operation 99 hystologic specimens of anastomotic wound were examined in order to investigate the healing of the anastomotic wounds, inflammation and terms of mucosal membrane healing. Resul ts. O n 2 days after the surgery inflammation signs and marginal necroses with microabscesses formation in wound edges were determined. Inflammation signs were observed in all tissue layers of anastomotic wound. On 6 days after the operation initial epithelization of anastomotic wound was determined. Regeneration signs and formation of collagenous fibers in the wound area with intensive connective tissue growth and productive inflammation around suture material were determined also. On 30 days after the operation wound epithelization with signs of productive inflammation around suture material was observed. Conclus ion. In our opinion significant destruction of wound edges on 2 day and delayed epithelization on 6 days after the surgery was related to massive bacterial infection of anastomotic wound. Absence of connective tissue in the anastomosis was possible due to anastomosis healing by primary tension. We consider it as advantage of the developed suture.